Can AI Predict Pediatric Sepsis? - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2023)
Pediatric sepsis remains a formidable challenge in modern medicine, representing a leading cause of mortality and long-term morbidity in children worldwide [...
Keywords: AI in Pediatrics; Predict; Pediatric; Sepsis; Artificial Intelligence; Machine Learning; Healthcare